Respuesta :

Answer:

[tex]m = 1[/tex] -- Slope

[tex]y = x + 3[/tex] --- Equation

Step-by-step explanation:

Given

[tex](x_1,y_1) = (0,3)[/tex]

[tex](x_2,y_2) = (-4,-1)[/tex]

Required

The slope and the equation

The slope (m) is calculated using:

[tex]m=\frac{y_2 - y_1}{x_2 - x_1}[/tex]

[tex]m=\frac{-1-3}{-4- 0}[/tex]

[tex]m=\frac{-4}{-4}[/tex]

[tex]m = 1[/tex]

The equation is calculated using:

[tex]y = m(x - x_1) + y_1[/tex]

This gives:

[tex]y = 1(x - 0) + 3[/tex]

[tex]y = 1(x) + 3[/tex]

[tex]y = x + 3[/tex]